TI_GERICHTE 12.2007.225 vom 23. März 2009 , Lavoro - accordo di scioglimento - formalità - irrinunciabilità - TI Tribunale d'appello (2009)
Lavoro - accordo di scioglimento - formalità - irrinunciabilità